Angiopoietin-1 and Angiopoietin-2 Expression Imbalance Influence in Early Period After Subarachnoid Hemorrhage - Gu, Hua (Int Neurourol J, 2016)
PURPOSE: Microvascular endothelial integrity is important for maintaining the blood-brain barrier (BBB). However, subarachnoid hemorrhage (SAH) disrupts this integrity, making the BBB dysfunctional—an important pathophysiological change after SAH. Angiopoietin-1 (Ang-1) and angiopoietin-2 (Ang-2) regulate microvascular permeability by balancing each other’s expression. METHODS: This study investigated the dynamics of Ang-1 and Ang-2 expression after SAH and the protective effect of Ang-1 on BBB functioning using an endovascular puncture model of rat SAH. The Ang-1 and Ang-2 expression in brain tissue was determined by immunohistochemistry. In addition, Western blotting was used to estimate Ang-1 and Ang-2 concentration and to compare them at 6–72 hours post-SAH cortex and hippocampus. Evans blue viability assay was used to evaluate BBB permeability, and neurological testing was implemented to evaluate neurological impairment during SAH. RESULTS: It was found that following SAH, Ang-1 expression decreases and Ang-2 expression increases in the cortex, hippocampus, and microvessels. The Ang-1/Ang-2 ratio decreased as quickly as 6 hours after SAH and reached its lowest 1 day after SAH. Finally, it was found that exogenous Ang-1 reduces SAH-associated BBB leakage and improves neurological function in post-SAH rats. CONCLUSIONS: Our findings suggest that the equilibrium between Ang-1 and Ang-2 is broken in a period shortly after SAH, and the treatment of exogenous Ang-1 injection alleviates neurological dysfunctions through decreasing BBB destruction.